ENSO‐Influenced Drought Drives Methane Flux Dynamics in a Tropical Wet Forest Soil. Issue 7 (22nd July 2019) - Aronson, E. L.; Dierick, D.; Botthoff, J. K.; Oberbauer, S.; Zelikova, T. J.; Harmon, T. C.; Rundel, P.; Johnson, R. F.; Swanson, A. C.; Pinto‐Tomás, A. A.; Artavia‐León, A.; Matarrita‐Carranza, B.; et al.
Abstract: Global atmospheric methane growth rates have wildly fluctuated over the past three decades, which may be driven by the proportion of tropical land surface saturated by water. The El Niño/Southern Oscillation Event (ENSO) cycle drives large‐scale climatic trends globally, with El Niño events typically bringing drier weather than La Niña. In a lowland tropical wet forest in Costa Rica, we measured methane flux bimonthly from March 2016 to June 2017 and using an automated chamber system. We observed a strong drying trend for several weeks during the El Niño in 2016, reducing soil moisture below normal levels. In contrast, soil conditions had high water content prior to the drought and during the moderate La Niña that followed. Soil moisture varied across the period studied and significantly impacted methane flux. Methane consumption was greater during the driest part of the El Niño period, while during La Niña and other time periods, soils had lower methane consumption. The mean methane flux observed was −0.022 mg CH4 ‐C m −2 hr −1, and methane was consumed at all timepoints, with lower consumption in saturated soils. Our data show that month studied, and the correlation between soil type and month significantly drove methane flux trends. Our data indicate that ENSO cycles may impact biogenic methane fluxes, mediated by soil moisture conditions. Climate projections for Central America show dryer conditions and increased El Niño frequency, further exacerbating predicted drought. These trends may lead to negative climate feedbacks, with drier conditions increasing soil methane consumption from the atmosphere. Key Points: We measured methane flux in a Costa Rican lowland tropical wet forest through a severe drought during the end of the 2015‐2016 El Niño Soil moisture varied across the El Niño and into the following La Niña and significantly impacted methane flux Predicted drying of the tropics may lead to negative climate feedbacks, which could increase soil methane consumption